2018
DOI: 10.3758/s13414-018-1513-z
|View full text |Cite
|
Sign up to set email alerts
|

Reward history but not search history explains value-driven attentional capture

Abstract: In past years, an extensive amount of research has focused on how past experiences guide future attention. Humans automatically attend to stimuli previously associated with reward and stimuli that have been experienced during visual search, even when it is disadvantageous in present situations. Recently, the relationship between "reward history" and "search history" has been discussed critically. We review results from research on value-driven attentional capture (VDAC) with a focus on these two experience-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 70 publications
2
17
0
Order By: Relevance
“…However, this prediction is in agreement with a growing body of evidence in human psychophysics studies, which document exactly this type of disadvantageous attentional capture of nonsalient rewarded stimuli ( Libera and Chelazzi 2009 ; Hickey and Van Zoest 2012 ; Failing and Theeuwes 2017 ; Le Pelley et al. 2017 ; Marchner and Preuschhof 2018 ). This unconscious attentional capture can take place even after delays of several months from the original reward association event ( Anderson and Yantis 2013 ).…”
Section: Introductionsupporting
confidence: 87%
“…However, this prediction is in agreement with a growing body of evidence in human psychophysics studies, which document exactly this type of disadvantageous attentional capture of nonsalient rewarded stimuli ( Libera and Chelazzi 2009 ; Hickey and Van Zoest 2012 ; Failing and Theeuwes 2017 ; Le Pelley et al. 2017 ; Marchner and Preuschhof 2018 ). This unconscious attentional capture can take place even after delays of several months from the original reward association event ( Anderson and Yantis 2013 ).…”
Section: Introductionsupporting
confidence: 87%
“…Moreover, rewarded ($0.25 on 80% of correct responses trials and $0.10 on 20% of correct responses) and non-rewarded (always followed by $0.00) colors differed in certainty of the outcome during training, and results could be interpreted as reflecting uncertainty associations rather than reward. However, participants showed larger capture to rewarded stimuli even though their predictive value was lower, suggesting that attention bias toward stimuli with more certain outcomes (e.g., Marchner & Preuschhof, 2018) was not driving the results. Other studies, however, have reported attention bias towards less certain stimuli (e.g., Le Pelley et al, 2018), but even in that study reward association influenced attention bias to a greater degree than uncertainty.…”
Section: Discussionmentioning
confidence: 89%
“…Note here that our use of the terms Bbottom-up^and Btop-down^is distinct from our use of the terms Blow-levelâ nd Bhigh-level.^The idea that bottom-up guidance refers only to low-level, stimulus-driven attention is outdated and does not stand up to scrutiny (Anderson, 2013;Awh, Belopolsky, & Theeuwes, 2012). It has been shown that high-level knowledge, such as memory of past reward associations (Anderson, 2013;Awh et al, 2012;Marchner & Preuschhof, 2018), also drives attention automatically in a Bbottom-up^manner. Thus, here we use the term Bbottom-up^to refer to this feedforward automatic mode of attentional guidance, and we use the term Btop-down^to refer to a more explicit mode of exploration.…”
mentioning
confidence: 97%